INTANGIBLE CULTURAL CONSERVATION AND NATURE PROTECTION THROUGH SPIRITUALISM IN UTTARAKHAND - Sahani, Ashok Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Identity of every civilization is associate with its cultural heritage, In every human societies it is found that protection of nature and its natural resources in different forms. In prehistoric era Man lives in the lap of nature and nature worship is known as naturism which is the ancient form of religion. Worship to Sun, Moon, Earth, Mountains are found in every civilization since past. Nature worship is often considered the primitive source of modern religious believes. Common to most forms of nature worship is a spiritual focus on the individual’s connection and influence on some aspects of the natural world and reverence towards religion. The reverence for these deified natural forces was expressed through various rituals, including food offerings, sacrifices, and festivals. Sacred groves were considered the dwelling places of these deities, and entering such spaces was often restricted to priests or those performing rituals. The concept of Prakriti, or nature, in Hindu philosophy further emphasizes the divine nature of the natural world. Rituals often involve offerings to rivers, trees, and mountains, which are seen as embodiments of the divine feminine energy popularly known as Shakti.